VD_FINDINFO HC / 2019 / 723 vom 8. Juli 2019 - VD Tribunal cantonal (2019)
BAIL À LOYER, LOYER INITIAL, RÉSILIATION, LÉGITIMATION ACTIVE ET PASSIVE | 264 CO, 269 CO, 317 al. 1 CPC (CH), 59 al. 2 CPC (CH), 59 al. 2 let. a CPC (CH)